The Development of the Mindful Parenting Scale for Indonesian Parents - Juaninda, Carrenina Prilly; Dumbi, Khairunnisa Fahira; Maulina, Dewi; Amanda, Aliyya (Psychological Research on Urban Society, 2025)
Mindful parenting benefits both parents and children; however, Indonesia lacks a valid and reliable tool for it. This study aims to develop a mindful parenting scale (MPS) as an effective tool for parents of children aged 3–6 years. The MPS is a multidimensional scale comprising five dimensions based on the theories of previous researchers (Kabat-Zinn and Kabat-Zinn and Duncan et al.). The study involved 326 participants with marriage durations of 2–32 years (M = 8.4, SD = 4.53). The results demonstrate that the final version of the MPS exhibits high internal consistency for the total score and each dimension. Additionally, confirmatory factor analysis confirmed that the multidimensional MPS aligns well with the model and possesses good convergent validity. The development of the MPS is crucial for researchers and practitioners in further to better understand, assess, and design interventions related to mindful parenting.